2021
DOI: 10.1136/bmj.m4858
|View full text |Cite|
|
Sign up to set email alerts
|

Home and Online Management and Evaluation of Blood Pressure (HOME BP) using a digital intervention in poorly controlled hypertension: randomised controlled trial

Abstract: Objective The HOME BP (Home and Online Management and Evaluation of Blood Pressure) trial aimed to test a digital intervention for hypertension management in primary care by combining self-monitoring of blood pressure with guided self-management. Design Unmasked randomised controlled trial with automated ascertainment of primary endpoint. Setting 76 general practices in the United Kingdom. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
164
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(192 citation statements)
references
References 42 publications
3
164
0
1
Order By: Relevance
“…In this trial, practitioners initiated medication escalation in response to 53% of recommendations, which is comparable to a previous hypertension tele-monitoring trial in which medication escalations were patient-initiated (55%) [12], and exceeds a US telemonitoring trial in which physicians initiated 41% of recommended changes [31]. However, despite only moderate adherence to medication escalations, the RCT found that HOME BP did significantly reduce blood pressure in the intervention group [12]. Therefore, is moderate adherence to medication escalation sufficient, or even optimal, and could cases of non-adherence be described as innovation rather than subversion?…”
Section: Distinguishing Non-adherence From Appropriate Adaptationsupporting
confidence: 50%
See 2 more Smart Citations
“…In this trial, practitioners initiated medication escalation in response to 53% of recommendations, which is comparable to a previous hypertension tele-monitoring trial in which medication escalations were patient-initiated (55%) [12], and exceeds a US telemonitoring trial in which physicians initiated 41% of recommended changes [31]. However, despite only moderate adherence to medication escalations, the RCT found that HOME BP did significantly reduce blood pressure in the intervention group [12]. Therefore, is moderate adherence to medication escalation sufficient, or even optimal, and could cases of non-adherence be described as innovation rather than subversion?…”
Section: Distinguishing Non-adherence From Appropriate Adaptationsupporting
confidence: 50%
“…A challenge for process evaluations is distinguishing between innovative adaptations to account for contextual variation and subversion or infidelity to intervention procedures [14]. In this trial, practitioners initiated medication escalation in response to 53% of recommendations, which is comparable to a previous hypertension tele-monitoring trial in which medication escalations were patient-initiated (55%) [12], and exceeds a US telemonitoring trial in which physicians initiated 41% of recommended changes [31]. However, despite only moderate adherence to medication escalations, the RCT found that HOME BP did significantly reduce blood pressure in the intervention group [12].…”
Section: Distinguishing Non-adherence From Appropriate Adaptationmentioning
confidence: 88%
See 1 more Smart Citation
“… 5 More recently, parts of this process were leveraged in a related trial utilizing a digital intervention. 8 …”
Section: Antihypertensive Self-titrationmentioning
confidence: 99%
“…HBPM is known to be effective in improving patient adherence, allowing patients to engage in self-management or self-monitoring of BP 12 . Because differences in perceiving BP levels between patients and physicians are evident, HBPM may play an important role in achieving a common understanding of the diagnosis and treatment of hypertension between patients and physicians 13 .…”
Section: Introductionmentioning
confidence: 99%